Discovering chemistry - Cooper, Elizabeth K. (New York, Harcourt, Brace, 1959)
An introduction to the principles of chemistry, with explanations of the chemical elements, molecular structure, and the writing of formulas. Suggests experiments that may safely be performed at home.
Keywords: Chemistry -- Juvenile literature; Chemistry; Chemistry -- Experiments